Cluster analysis on the example of work data of the National Power System. Part 2. Research and selected results - Tchórzewski, Jerzy; Kania, Tomasz (Studia Informatica. System and information technology, 2021)
The work is a continuation of the article under the same main title and subtitle Part 1. Comparative study of methods and conditions. This article concerns the cluster analysis, which was carried out on the example of data concerning the operation of the National Power System, namely thetotal generations of nCDGUs and CDGUs listed by PSE Operator. Two algorithms were used to obtain the results of the cluster analysis, i.e. the Ward algorithm and the algorithm of self-organizing twodimensional topographic maps. The obtained results were interpreted and their discussion and interpretation were conducted.